Sodium-ion battery positive electrode material, precursor and preparation method thereof, sodium-ion battery and power-related equipment
By introducing core-coated sulfide and phosphide layers into the positive electrode material of sodium ion battery and performing titanium ion doping, the problem of poor cyclic stability and conductivity of NFM materials is solved, and higher battery stability and conductivity are achieved, and battery life is extended.
Patent Information
- Application Number
- CN202510562758.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-08-05
AI Technical Summary
The existing nickel ferromanganese (NFM) materials have poor performance in cycling stability, conductivity and electrochemical properties in sodium ion batteries, and they need to be optimized through structural regulation and synthesis process to improve their performance.
The precursor design of the sodium ion battery positive electrode material with core coated sulfide and phosphide is used to enhance the crystal structure stability through titanium ion doping, and improve the conductivity and corrosion resistance through the sulfide and phosphide layers, reducing the interface impedance.
It improves the cyclic stability and conductivity of the positive electrode material of sodium ion battery, extends the service life of the battery, reduces the interface impedance, and enhances the electrochemical performance of the battery.
Smart Images

Figure CN120432487A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery positive electrode material and its precursor and preparation method, a sodium ion battery and electrical equipment. Background Art
[0002] Nickel-cobalt-manganese (NCM) materials offer excellent electrochemical performance in lithium-ion battery cathodes, but the cobalt they use is expensive and scarce. To reduce costs and enhance sustainability, nickel-iron-manganese (NFM) materials are gaining increasing attention as an alternative.
[0003] However, the existing NFM materials do not perform well in terms of cycle stability, conductivity and electrochemical performance, and their performance needs to be improved through structural regulation and synthesis process optimization.
[0004] Therefore, it is of great significance to develop a nickel-iron-manganese ternary material with excellent performance and its preparation method. Summary of the Invention
[0005] The purpose of this application is to provide a sodium ion battery positive electrode material precursor, a sodium ion battery positive electrode material and a preparation method thereof, a sodium ion battery and electrical-related equipment to solve the above problems.
[0006] To achieve the above objectives, the present application provides, in a first aspect, a sodium ion battery cathode material precursor, comprising a core, a first coating layer, and a second coating layer;
[0007] The first coating layer covers the core;
[0008] The second coating layer covers the first coating layer;
[0009] The first coating layer includes sulfide;
[0010] The second coating layer includes a phosphide;
[0011] The chemical formula of the core is Ni a Fe b Mn c Ti d (OH)2, a+b+c+d=1, 0.3≤a≤0.5, 0.1≤b≤0.35, 0.2≤c≤0.4, 0.001≤d≤0.05.
[0012] Optionally, the sodium ion battery cathode material precursor meets at least one of the following conditions:
[0013] A. The sulfide includes ferrous sulfide, nickel sulfide, manganese sulfide, and titanium sulfide;
[0014] B. The phosphide includes ferrous phosphate, nickel phosphate, manganese phosphate, and titanium phosphate;
[0015] C. The D50 of the core is 8 μm-12 μm;
[0016] D. the thickness of the first coating layer is 0.01 μm-1 μm;
[0017] E. The thickness of the second coating layer is 0.01 μm-1 μm;
[0018] F. The TD of the sodium ion battery cathode material precursor is 2 g / cm 3 -2.3g / cm 3 ;
[0019] G. The D50 of the sodium ion battery positive electrode material precursor is 9 μm-12 μm.
[0020] The second aspect of the present application provides a method for preparing the sodium ion battery positive electrode material precursor, comprising:
[0021] The iron source, nickel source, manganese source and titanium source are first mixed to obtain a mixed metal salt solution;
[0022] The mixed metal salt solution, sodium hydroxide, and base solution are mixed for a second time, and a first reaction is performed to generate a solid product A;
[0023] The solid product A is subjected to a first heating to obtain a solid product B;
[0024] Under a sulfur-containing atmosphere, the solid product B is subjected to a second heating to obtain a solid product C;
[0025] The solid product C and the phosphate solution are mixed for a third time, and then reacted for a second time to obtain a solid product D;
[0026] The solid product D is washed and dried to obtain a precursor of a positive electrode material for a sodium ion battery.
[0027] Optionally, the method for preparing the sodium ion battery cathode material precursor satisfies at least one of the following conditions:
[0028] A. The iron source includes ferrous sulfate heptahydrate;
[0029] B. the nickel source comprises nickel sulfate;
[0030] C. the manganese source comprises manganese sulfate;
[0031] D. The titanium source includes Ti(SO4)2, Ti(S2O7)2, TiO(SO4), Ti4O5(SO4)3, Ti7O 13(SO4), Ti2O3(SO4), TiBr4, TiCl4;
[0032] E. the base liquid includes aqueous ammonia;
[0033] F. The sulfur-containing gas in the sulfur-containing atmosphere includes one or more of hydrogen sulfide, sulfur dioxide, and carbon disulfide;
[0034] G. the phosphate solution comprises a sodium phosphate solution;
[0035] H. The washing adopts a detergent, and the detergent comprises water and / or ethanol.
[0036] Optionally, the method for preparing the sodium ion battery cathode material precursor satisfies at least one of the following conditions:
[0037] A. the pH value of the first mixture is 10-11.5;
[0038] B. the metal ion concentration of the mixed metal salt solution is 0.3 mol / L-0.5 mol / L;
[0039] C. The flow rate of the mixed metal salt solution is 0.5 mL / min-2 mL / min;
[0040] D. The solid-to-liquid ratio of the solid product B to the phosphate solution is 1 g: (10 mL-15 mL);
[0041] E. The temperature of the first reaction is 55°C-65°C and the time is 18h-36h;
[0042] F. the first heating comprises microwave heating;
[0043] G. the first heating temperature is 120°C-170°C, and the time is 1h-8h;
[0044] H. the second heating temperature is 100°C-120°C, and the time is 1h-4h;
[0045] I. The temperature of the second reaction is 60°C-80°C and the time is 0.5h-6h;
[0046] J. The drying temperature is 80°C-100°C and the drying time is 12h-24h.
[0047] In a third aspect, the present application provides a sodium ion battery positive electrode material, comprising the sodium ion battery positive electrode material precursor or the sodium ion battery positive electrode material precursor prepared by the preparation method of the sodium ion battery positive electrode material precursor.
[0048] A fourth aspect of the present application provides a method for preparing a positive electrode material for a sodium ion battery, comprising:
[0049] The sodium ion battery positive electrode material precursor or the sodium ion battery positive electrode material precursor prepared by the preparation method of the sodium ion battery positive electrode material precursor and sodium salt are mixed and calcined to obtain a sodium ion battery positive electrode material.
[0050] Optionally, the method for preparing the sodium ion battery positive electrode material satisfies at least one of the following conditions:
[0051] A. The sodium salt includes sodium carbonate and / or sodium hydroxide;
[0052] B. The molar ratio of the sodium ion battery positive electrode material precursor to the sodium salt is 1:1.05-1.1;
[0053] C. The calcination temperature rise rate is 3°C / min-5°C / min, the end temperature is 800°C-900°C, and the calcination time is 24h-36h.
[0054] In a fifth aspect, the present application provides a sodium ion battery, comprising the sodium ion battery positive electrode material or the sodium ion battery positive electrode material prepared by the method for preparing the sodium ion battery positive electrode material.
[0055] The sixth aspect of the present application provides an electrical device, including the sodium ion battery.
[0056] Compared with the prior art, the advantages of this application include:
[0057] The sodium ion battery positive electrode material precursor provided by the present application enhances the crystal structure stability of the sodium ion battery positive electrode material precursor and improves the charge conduction efficiency through titanium ion doping, so that it has a better cycle life under high rate conditions; the iron sulfide layer in the first coating layer increases the conductivity of the material, and the phosphide layer in the second coating layer improves the corrosion resistance, effectively reduces the interfacial impedance, and can further enhance the electrical conductivity of the material, can isolate the positive electrode material from direct contact with the electrolyte, avoid corrosion and failure of the positive electrode material, and effectively improve the cycle stability of the battery.
[0058] The preparation method of the sodium ion battery positive electrode material precursor provided in the present application has readily available raw materials and simple procedures.
[0059] The sodium ion battery positive electrode material provided in this application has strong conductivity and good cycle stability.
[0060] The method for preparing a positive electrode material for a sodium ion battery provided in the present application has a simple preparation process, and the obtained positive electrode material for a sodium ion battery has good electrochemical performance.
[0061] The sodium ion battery and electrical equipment provided in this application have a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0063] Figure 1 This is a scanning electron microscope image of the sodium ion battery cathode material precursor prepared in Example 1;
[0064] Figure 2 This is a scanning electron microscope image of the sodium ion battery positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0065] As used herein:
[0066] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variations thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0067] The conjunction "consisting of" excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed, excluding materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim, rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0068] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed alone. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0069] In these examples, parts and percentages are by mass unless otherwise indicated.
[0070] "Parts by mass" refers to the basic unit of measurement used to express the mass ratio of multiple components. One part can represent any unit of mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, this means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, we could say that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number representing a multiplication factor). It's important to note that, unlike parts by mass, the sum of the mass of all components is not limited to 100 parts.
[0071] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0072] In a first aspect, the present application provides a sodium ion battery cathode material precursor, comprising a core, a first coating layer, and a second coating layer;
[0073] The first coating layer covers the core;
[0074] The second coating layer covers the first coating layer;
[0075] The first coating layer includes sulfide;
[0076] The second coating layer includes a phosphide;
[0077] The chemical formula of the core is Ni a Fe b Mn c Ti d (OH)2, a+b+c+d=1, 0.3≤a≤0.5, 0.1≤b≤0.35, 0.2≤c≤0.4, 0.001≤d≤0.05.
[0078] Optionally, a can be 0.3, 0.4, 0.5 or any value between 0.3-0.5, b can be 0.1, 0.2, 0.3, 0.35 or any value between 0.1-0.35, c can be 0.2, 0.3, 0.4 or any value between 0.2-0.4, and d can be 0.001, 0.01, 0.05 or any value between 0.001-0.05.
[0079] It should be noted that the element ratio within this range can ensure that the sodium ion battery positive electrode material precursor achieves optimized effects in terms of conductivity, stability, capacity, etc.
[0080] It should also be noted that the introduction of titanium ion doping can replace part of the manganese or iron position with titanium, thereby forming a more stable lattice structure. This is because Ti4+ The introduction of can partially replace Fe 3+ or Mn 3+ , reducing lattice distortion, making the lattice more symmetrical and stable, thereby reducing structural changes; while Ti 4+ It has a stable chemical valence and is not prone to redox reactions, which helps maintain the stability of the material during the charging and discharging process, thereby improving the reduction stability of the material. In addition, the chemical bonds of titanium can improve the electron conduction path, thereby improving the overall conductivity of the material.
[0081] In some embodiments, the sodium ion battery cathode material precursor satisfies at least one of the following conditions:
[0082] A. The sulfides include ferrous sulfide, nickel sulfide, manganese sulfide, and titanium sulfide; B. The phosphides include ferrous phosphate, nickel phosphate, manganese phosphate, and titanium phosphate;
[0083] C. The D50 of the core is 8 μm-12 μm;
[0084] Optionally, the D50 of the core may be 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or any value between 8 μm and 12 μm;
[0085] D. the thickness of the first coating layer is 0.01 μm-1 μm;
[0086] Optionally, the thickness of the first coating layer may be 0.01 μm, 0.05 μm, 1 μm, or any value between 0.01 μm and 1 μm;
[0087] E. The thickness of the second coating layer is 0.01 μm-1 μm;
[0088] Optionally, the thickness of the second coating layer may be 0.01 μm, 0.05 μm, 1 μm, or any value between 0.01 μm and 1 μm;
[0089] F. The TD of the sodium ion battery cathode material precursor is 2 g / cm 3 -2.3g / cm 3 ;
[0090] Optionally, the TD of the precursor of the positive electrode material for sodium ion batteries can be 2 g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 or 2g / cm 3 -2.3g / cm 3 Any value between
[0091] G. The D50 of the sodium ion battery positive electrode material precursor is 9 μm-12 μm.
[0092] Optionally, the D50 of the sodium ion battery positive electrode material precursor may be 9 μm, 10 μm, 11 μm, 12 μm, or any value between 9 μm and 12 μm.
[0093] The second aspect of the present application provides a method for preparing the sodium ion battery positive electrode material precursor, comprising:
[0094] The iron source, nickel source, manganese source and titanium source are first mixed to obtain a mixed metal salt solution;
[0095] The mixed metal salt solution, sodium hydroxide, and base solution are mixed for a second time, and a first reaction is performed to generate a solid product A;
[0096] The solid product A is subjected to a first heating to obtain a solid product B;
[0097] Under a sulfur-containing atmosphere, the solid product B is subjected to a second heating to obtain a solid product C;
[0098] The solid product C and the phosphate solution are mixed for a third time, and then reacted for a second time to obtain a solid product D;
[0099] The solid product D is washed and dried to obtain a precursor of a positive electrode material for a sodium ion battery.
[0100] It should be noted that the sulfurization treatment of solid product B can generate a sulfide layer on the surface of the material, improve the surface conductivity, and promote the rapid conduction of electrons and ions; the phosphide layer is regenerated on the surface of the already sulfurized solid product C, which increases the corrosion resistance of the material and further reduces the interfacial impedance. The sulfurization treatment first can ensure the enhanced conductivity, while the phosphating treatment forms a more stable protective layer on the sulfurized surface. The synergistic effect of the two significantly improves the electrochemical stability and conductivity of the sodium ion battery positive electrode material precursor.
[0101] In some embodiments, the method for preparing a sodium ion battery cathode material precursor satisfies at least one of the following conditions:
[0102] A. The iron source includes ferrous sulfate heptahydrate;
[0103] B. the nickel source comprises nickel sulfate;
[0104] C. the manganese source comprises manganese sulfate;
[0105] D. The titanium source includes Ti(SO4)2, Ti(S2O7)2, TiO(SO4), Ti4O5(SO4)3, Ti7O 13(SO4), Ti2O3(SO4), TiBr4, TiCl4;
[0106] E. the base liquid includes aqueous ammonia;
[0107] F. The sulfur-containing gas in the sulfur-containing atmosphere includes one or more of hydrogen sulfide, sulfur dioxide, and carbon disulfide;
[0108] G. the phosphate solution comprises a sodium phosphate solution;
[0109] H. The washing adopts a detergent, and the detergent comprises water and / or ethanol.
[0110] In some embodiments, the method for preparing a sodium ion battery cathode material precursor satisfies at least one of the following conditions:
[0111] A. the pH value of the first mixture is 10-11.5;
[0112] Optionally, the pH value of the first mixture may be 10.5, 11, 11.5, or any value between 10 and 11.5;
[0113] B. the metal ion concentration of the mixed metal salt solution is 0.3 mol / L-0.5 mol / L;
[0114] Optionally, the metal ion concentration of the mixed metal salt solution may be 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, or any value between 0.3 mol / L and 0.5 mol / L;
[0115] C. The flow rate of the mixed metal salt solution is 0.5 mL / min-2 mL / min;
[0116] Optionally, the flow rate of the mixed metal salt solution may be 0.5 mL / min, 1 mL / min, 1.5 mL / min, 2 mL / min, or any value between 0.5 mL / min and 2 mL / min;
[0117] It should be noted that when the flow rate of the mixed metal salt solution is 0.5mL / min-2mL / min, a slow flow rate will affect the extension of the reaction time, while a too fast flow rate will not result in sufficient reaction, and the flow rate will further affect the particle size, morphology, size, and crystallinity of the material;
[0118] D. The solid-to-liquid ratio of the solid product B to the phosphate solution is 1 g: (10 mL-15 mL);
[0119] Optionally, the solid-to-liquid ratio of the solid product B to the phosphate solution can be 1 g:10 mL, 1 g:11 mL, 1 g:12 mL, 1 g:13 mL, 1 g:14 mL, 1 g:15 mL or any value between 1 g:(10 mL-15 mL);
[0120] E. The temperature of the first reaction is 55°C-65°C and the time is 18h-36h;
[0121] Optionally, the temperature of the first reaction can be 55°C, 60°C, 65°C or any value between 55°C and 65°C, and the time can be 18h, 20h, 25h, 30h, 35h, 36h or any value between 18h and 36h;
[0122] F. the first heating comprises microwave heating;
[0123] It should be noted that microwave heating can heat materials quickly and evenly in a short period of time, reducing temperature gradients. Microwave heating can also promote uniform nucleation and growth in crystals, which is conducive to the formation of a uniform crystalline structure. Compared with traditional electric blast heating, microwave heating can reduce heat loss and improve energy utilization.
[0124] G. the first heating temperature is 120°C-170°C, and the time is 1h-8h;
[0125] Optionally, the first heating temperature may be 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., or any value between 120° C. and 170° C., and the first heating time may be 1 h, 2 h, 4 h, 6 h, 8 h, or any value between 1 h and 8 h.
[0126] H. the second heating temperature is 100°C-120°C, and the time is 1h-4h;
[0127] Optionally, the second heating temperature may be 100° C., 110° C., 120° C., or any value between 100° C. and 120° C., and the second heating time may be 1 hour, 2 hours, 3 hours, 4 hours, or any value between 1 hour and 4 hours;
[0128] It should be noted that when hydrogen sulfide (H2S) gas is introduced at low temperature (100℃-120℃), some of the hydrogen sulfide gas will adhere to the surface of the precursor material and react with the metal elements in the precursor material as follows:
[0129] Fe(OH)2+H2S==FeS+H2O;
[0130] Ni(OH)2+H2S==NiS+H2O;
[0131] Mn(OH)2+H2S==MnS+H2O;
[0132] Ti(OH)2+H2S==TiS+H2O;
[0133] Under the same reaction conditions, the Gibbs free energy of the four products is △Gf(FeS)<△Gf(MnS)<△Gf(TiS)<△Gf(NiS). Therefore, FeS accounts for the highest proportion in the sulfide layer formed on the surface.
[0134] I. The temperature of the second reaction is 60°C-80°C and the time is 0.5h-6h;
[0135] Optionally, the temperature of the second reaction can be 60°C, 70°C, 80°C or any value between 60°C and 80°C, and the time can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h or any value between 0.5h and 6h;
[0136] J. The drying temperature is 80°C-100°C and the drying time is 12h-24h.
[0137] Optionally, the drying temperature can be 80°C, 90°C, 100°C or any value between 80°C and 100°C, and the drying time can be 12h, 16h, 18h, 20h, 22h, 24h or any value between 12h and 24h.
[0138] In a third aspect, the present application provides a sodium ion battery positive electrode material, comprising the sodium ion battery positive electrode material precursor or the sodium ion battery positive electrode material precursor prepared by the preparation method of the sodium ion battery positive electrode material precursor.
[0139] A fourth aspect of the present application provides a method for preparing a positive electrode material for a sodium ion battery, comprising:
[0140] The sodium ion battery positive electrode material precursor or the sodium ion battery positive electrode material precursor prepared by the preparation method of the sodium ion battery positive electrode material precursor and sodium salt are mixed and calcined to obtain a sodium ion battery positive electrode material.
[0141] In some embodiments, the method for preparing the sodium ion battery positive electrode material satisfies at least one of the following conditions:
[0142] A. The sodium salt includes sodium carbonate and / or sodium hydroxide;
[0143] B. The molar ratio of the sodium ion battery positive electrode material precursor to the sodium salt is 1:1.05-1.1;
[0144] Optionally, the molar ratio of the sodium ion battery cathode material precursor to the sodium salt can be 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, 1:1.1 or any value between 1:1.05 and 1.1;
[0145] It should be noted that when the molar ratio of the precursor of the positive electrode material of the sodium ion battery and the sodium salt is 1:1.05-1.1, it is necessary to ensure that the material can be synthesized to avoid the incorrect proportion of the synthetic material components due to insufficient sodium carbonate, and to avoid excessive sodium carbonate, which leads to excessive residual alkali in the material;
[0146] C. The calcination temperature rise rate is 3°C / min-5°C / min, the end temperature is 800°C-900°C, and the calcination time is 24h-36h.
[0147] Optionally, the heating rate of the calcination can be 3°C / min, 4°C / min, 5°C / min or any value between 3°C / min and 5°C / min, and the end temperature can be 800°C, 850°C, 900°C or any value between 800°C and 900°C.
[0148] In a fifth aspect, the present application provides a sodium ion battery, comprising the sodium ion battery positive electrode material or the sodium ion battery positive electrode material prepared by the method for preparing the sodium ion battery positive electrode material.
[0149] The sixth aspect of the present application provides an electrical device, including the sodium ion battery.
[0150] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, the conditions are carried out according to conventional conditions or manufacturer recommendations. The reagents or instruments used are not specified by the manufacturer and are conventional products that can be purchased commercially.
[0151] Example 1
[0152] The first aspect of the present embodiment provides a sodium ion battery positive electrode material precursor, comprising a core, a first coating layer and a second coating layer; the first coating layer covers the core; the second coating layer covers the first coating layer; the first coating layer is a sulfide, and the sulfide includes ferrous sulfide, nickel sulfide, manganese sulfide, and titanium sulfide; the second coating layer is a phosphide, and the phosphide is ferrous phosphate, nickel phosphate, manganese phosphate, and titanium phosphate; the chemical formula of the core is Ni a Fe b Mn c Ti d (OH)2, a+b+c+d=1, a=0.35, b=0.32, c=0.32, d=0.01;
[0153] A second aspect of this embodiment provides a method for preparing a sodium ion battery positive electrode material precursor, comprising:
[0154] S1: With the mass proportions of metal elements nickel (Ni), iron (Fe), manganese (Mn), and titanium (Ti) being 35%, 32%, 32%, and 1% respectively, weigh the corresponding masses of ferrous sulfate heptahydrate, nickel sulfate hexahydrate, manganese sulfate monohydrate, and Ti(SO4)2 to prepare a mixed metal salt solution with a total metal mass concentration of 0.3 mol / L;
[0155] S2: Add 0.5 L of mixed metal salt solution and sodium hydroxide solution to 1.6 L of ammonia base solution at a flow rate of 0.5 mL / min, ensuring that the pH value of the mixed system is 10.5 during the addition. After the addition is completed, a coprecipitation reaction is carried out at 60°C for 18 hours to produce solid product A;
[0156] S3: placing the obtained solid product A in a microwave heating device and heating at 150° C. for 2 hours to obtain a solid product B;
[0157] S4: placing the solid product B in a tube furnace, first introducing Ar and heating to 120°C, then replacing Ar with hydrogen sulfide gas for mild sulfidation treatment, the reaction time is 2 hours, to obtain a solid product C;
[0158] S5: Immerse the solid product C in a 0.5 M sodium phosphate solution at a solid-liquid ratio of 1 g:10 mL for phosphating at 70°C for 1 hour to obtain a solid product D;
[0159] S6: The solid product D was washed alternately with deionized water and ethanol six times to remove unreacted products, and then dried at 80° C. for 12 hours to obtain a precursor of a sodium ion battery positive electrode material.
[0160] The scanning electron microscopy of the sodium ion battery cathode material precursor is as follows Figure 1 shown.
[0161] A third aspect of this embodiment provides a sodium ion battery positive electrode material and a preparation method thereof, comprising:
[0162] The sodium ion battery positive electrode material precursor obtained above was evenly mixed with sodium carbonate in a molar ratio of 1:1.05, and the mixture was sintered at 850°C for 24 hours at a heating rate of 3°C / min. After cooling, the mixture was crushed and sieved to obtain a sodium ion battery positive electrode material.
[0163] The scanning electron microscopy of the sodium ion battery cathode material is shown in Figure 2. Figure 2 shown.
[0164] A fourth aspect of this embodiment provides a sodium ion battery, wherein the above-mentioned sodium ion battery positive electrode material is assembled into a button cell battery.
[0165] Example 2
[0166] The difference from Example 1 is that the mass proportions of the metal elements nickel (Ni), iron (Fe), manganese (Mn), and titanium (Ti) are 50%, 20%, 29%, and 1%, respectively.
[0167] Example 3
[0168] The difference from Example 1 is that the mass proportions of the metal elements nickel (Ni), iron (Fe), manganese (Mn), and titanium (Ti) are 50%, 20%, 29.9%, and 0.1%, respectively.
[0169] Example 4
[0170] The difference from Example 1 is that the mass proportions of the metal elements nickel (Ni), iron (Fe), manganese (Mn), and titanium (Ti) are 50%, 20%, 27%, and 3%, respectively.
[0171] Example 5
[0172] The difference from Example 1 is that the mass proportions of the metal elements nickel (Ni), iron (Fe), manganese (Mn), and titanium (Ti) are 50%, 20%, 25%, and 5%, respectively.
[0173] Comparative Example 1
[0174] The difference from Example 1 is that Ti(SO4)2 is not added.
[0175] Comparative Example 2
[0176] The difference from Example 1 is that no vulcanization treatment is performed.
[0177] Comparative Example 3
[0178] The difference from Example 1 is that no phosphating reaction is performed.
[0179] Comparative Example 4
[0180] The difference from Example 1 is that the phosphating reaction is carried out first and then the sulfurization treatment is carried out.
[0181] The prepared sodium ion battery cathode material precursor was subjected to physical and chemical performance tests, and the specific test results are shown in Table 1.
[0182] Table 1 Physical and chemical properties test
[0183]
[0184] The electrochemical performance of the button cell prepared above was tested in the voltage range of 2-4.2 V. The specific test results are shown in Table 2.
[0185] Table 2 Electrochemical performance test
[0186]
[0187] From the above results, it can be seen that under the same conditions, 0.1C discharge, ICE, 1C discharge, and 100 cycles capacity retention at 1C, the electrochemical performance of Examples 1-5 are superior to those of Examples 1-4. By performing the first and second coatings on the precursor and titanium doping, the performance of the material is significantly improved.
[0188] In terms of material physical properties, Examples 1-5 improve the tap density of the material, where the tap density is an important factor affecting the capacity of the sodium ion battery. Specifically, the more active material mass per unit volume, the higher the energy density of the sodium ion battery. Materials with higher tap density can fill more active material within a limited battery volume, thereby improving the volumetric capacity and discharge ratio of the battery.
[0189] In terms of the electrochemical properties of the material, Examples 1-5 enhance the conductivity of the material, which is clearly seen from the ICE and discharge gram capacity between Examples 1-5 and Comparative Examples 1-4. The corrosion resistance of the material is further improved after coating and titanium doping, which is clearly seen from the capacity retention rate between Examples 1-5 and Comparative Examples 1-4.
[0190] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
[0191] Furthermore, those skilled in the art will appreciate that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and to form distinct embodiments. For example, in the claims above, any of the claimed embodiments may be used in any combination. The information disclosed in this background section is intended solely to enhance understanding of the overall background of this application and should not be construed as an admission or any implication that such information constitutes prior art known to those skilled in the art.
Claims
1. A sodium ion battery cathode material precursor, characterized in that: comprising a core, a first cladding layer, and a second cladding layer; The first coating layer covers the core; The second coating layer covers the first coating layer; The first coating layer includes sulfide; The second coating layer includes a phosphide; The chemical formula of the core is Ni a Fe b Mn c Ti d (OH)2, a+b+c+d=1, 0.3≤a≤0.5, 0.1≤b≤0.35, 0.2≤c≤0.4, 0.001≤d≤0.
05.
2. The sodium ion battery cathode material precursor according to claim 1, characterized in that At least one of the following conditions is met: A. The sulfide includes ferrous sulfide, nickel sulfide, manganese sulfide, and titanium sulfide; B. The phosphide includes ferrous phosphate, nickel phosphate, manganese phosphate, and titanium phosphate; C. The D50 of the core is 8 μm-12 μm; D. the thickness of the first coating layer is 0.01 μm-1 μm; E. The thickness of the second coating layer is 0.01 μm-1 μm; F. The TD of the sodium ion battery cathode material precursor is 2 g / cm 3 -2.3g / cm 3 ; G. The D50 of the sodium ion battery positive electrode material precursor is 9 μm-12 μm.
3. A method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 1 or 2, characterized in that: include: The iron source, nickel source, manganese source and titanium source are first mixed to obtain a mixed metal salt solution; The mixed metal salt solution, sodium hydroxide, and base solution are mixed for a second time, and a first reaction is performed to generate a solid product A; The solid product A is subjected to a first heating to obtain a solid product B; Under a sulfur-containing atmosphere, the solid product B is subjected to a second heating to obtain a solid product C; The solid product C and the phosphate solution are mixed for a third time, and then reacted for a second time to obtain a solid product D; The solid product D is washed and dried to obtain a precursor of a positive electrode material for a sodium ion battery.
4. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 3, wherein: At least one of the following conditions is met: A. The iron source includes ferrous sulfate heptahydrate; B. the nickel source comprises nickel sulfate; C. the manganese source comprises manganese sulfate; D. The titanium source includes Ti(SO4)2, Ti(S2O7)2, TiO(SO4), Ti4O5(SO4)3, Ti7O 13 (SO4), Ti2O3(SO4), TiBr4, TiCl4; E. the base liquid includes aqueous ammonia; F. The sulfur-containing gas in the sulfur-containing atmosphere includes one or more of hydrogen sulfide, sulfur dioxide, and carbon disulfide; G. the phosphate solution comprises a sodium phosphate solution; H. The washing adopts a detergent, and the detergent comprises water and / or ethanol.
5. The method for preparing a sodium ion battery cathode material precursor according to claim 3 or 4, characterized in that: At least one of the following conditions is met: A. the pH value of the first mixture is 10-11.5; B. the metal ion concentration of the mixed metal salt solution is 0.3 mol / L-0.5 mol / L; C. The flow rate of the mixed metal salt solution is 0.5 mL / min-2 mL / min; D. The solid-to-liquid ratio of the solid product B to the phosphate solution is 1 g: (10 mL-15 mL); E. The temperature of the first reaction is 55°C-65°C and the time is 18h-36h; F. the first heating comprises microwave heating; G. the first heating temperature is 120°C-170°C, and the time is 1h-8h; H. the second heating temperature is 100°C-120°C, and the time is 1h-4h; I. The temperature of the second reaction is 60°C-80°C and the time is 0.5h-6h; J. The drying temperature is 80°C-100°C and the drying time is 12h-24h.
6. A sodium ion battery cathode material, characterized in that A sodium ion battery positive electrode material precursor comprising the sodium ion battery positive electrode material precursor according to claim 1 or 2 or a sodium ion battery positive electrode material precursor prepared by the preparation method of any one of claims 3-5.
7. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: include: The sodium ion battery positive electrode material precursor according to claim 1 or 2 or the sodium ion battery positive electrode material precursor prepared by the preparation method of any one of claims 3 to 5 and sodium salt are mixed and calcined to obtain a sodium ion battery positive electrode material.
8. The method for preparing a positive electrode material for a sodium ion battery according to claim 7, wherein: At least one of the following conditions is met: A. The sodium salt includes sodium carbonate and / or sodium hydroxide; B. The molar ratio of the sodium ion battery positive electrode material precursor to the sodium salt is 1:1.05-1.1; C. The calcination temperature rise rate is 3°C / min-5°C / min, the end temperature is 800°C-900°C, and the calcination time is 24h-36h.
9. A sodium ion battery, characterized in that: The sodium ion battery positive electrode material comprises the sodium ion battery positive electrode material according to claim 6 or the sodium ion battery positive electrode material prepared by the preparation method of the sodium ion battery positive electrode material according to claim 7 or 8.
10. An electrical equipment, characterized in that: Including the sodium ion battery according to claim 9.